The book of Joe : the life, wit, and (sometimes accidental) wisdom of Joe Biden - Wilser, Jeff (Three Rivers Press, 2017)
Structured around key moments in Biden's life and career--and filled with Biden-isms like "That's a bunch of malarkey" and "I may be Irish, but I'm not stupid"--this blend of biography, advice, and humor will reveal the experiences that forged Joe Biden, and the lessons we can use in our own lives. Along the way, readers will also encounter fun sidebars on his love of muscle cars, his most endearing gaffes, his bromance with President Obama, and much more.The aviators. The Amtrak. The ice cream cones. The memes. Few politicians are as iconic, or as beloved, as Joe Biden. Now, in The Book of Joe, Biden fans will finally have the definitive look at America's favorite vice president--and what he can teach us. Yet beneath the memorable Biden-isms, the book will reveal an inspirational story of a man who keeps "getting back up." We need this right now. Much as Biden has come back from both professional missteps and personal heartbreaks, sometimes we all have to get back up and fight. Given Biden's reputation as a decent, plainspoken, patriotic statesman of integrity, this entertaining and practical book will be both a celebration of great political figure and an essential guide to creating the America he believes in so dearly.